MEMORY AND COGNITIVE LEARNING STRATEGIES FROM THE TEACHERS AND LEARNERS PERSPECTIVES - Darin Nshiwi; Feisal Aziez; Hazim Alkhrisheh (STKIP PGRI Jombang, 2020)
This research falls within the area of language learning strategies (LLS) in English as a foreign language (EFL). Although the impact of LLS on vocabulary learning has attracted ample of studies in the field on teaching English as a second or foreign language. However, teachers and learners’ views of LLS have not been investigated enough. To that end, this research sheds light on the adopted approaches while teaching these strategies by EFL teachers at the Higher Language Institute. It investigates whether these strategies are taught implicitly, explicitly or both. To conduct this study, the researcher applied two questionnaires: the questionnaires are used to evaluate the used memory and cognitive strategies by teachers and intermediate learners at the HLI. These instruments are applied on the sample that includes 36 intermediate and 30 EFL teachers at the HLI. The data obtained was dealt with descriptively and analytically. The findings show that the majority of teachers tend to train students to use memory and cognitive strategies implicitly. In addition, it was noticed that both teachers and learners use the same set of strategies which implies that teaching approaches has a direct impact on the used strategies by the learners.